The detection of aquatic animal species using environmental DNA – a review of eDNA as a survey tool in ecology - Rees, Helen C.; Maddison, Ben C.; Middleditch, David J.; Patmore, James R.; Gough, Kevin C. (Wiley, 2014)
1. Knowledge of species distribution is critical to ecological management and conservation biology. Effective management requires the detection of populations, which can sometimes be at low densities and is usually based on visual detection and counting. 2. Recently, there has been considerable interest in the detection of short species-specific environmental DNA (eDNA) fragments to allow aquatic species monitoring within different environments due to the potential of greater sensitivity over traditional survey methods which can be time-consuming and costly. 3. Environmental DNA analysis is increasingly being used in the detection of rare or invasive species and has also been applied to eDNA persistence studies and estimations of species biomass and distribution. When combined with next-generation sequencing methods, it has been demonstrated that entire faunas can be identified. 4. Different environments require different sampling methodologies, but there remain areas where laboratory methodologies could be standardized to allow results to be compared across studies. 5. Synthesis and applications. We review recently published studies that use eDNA to moni- tor aquatic populations, discuss the methodologies used and the application of eDNA analysis as a survey tool in ecology. We include innovative ideas for how eDNA can be used for conservation and management citing test cases, for instance, the potential for on-site analyses, including the application of eDNA analysis to carbon nanotube platforms or laser transmission spectroscopy to facilitate rapid on-site detections. The use of eDNA monitoring is already being adopted in the UK for ecological surveys.